Correlation between Obesity and Socioeconomic and Psychological Characteristics of Students Attending Different Rural School Types - Stephan Gretschel; Annabell Morgner; Cornelia Schindler; Nina Amelie Zierenberg; Henry Kusian; Meike Herkner; Stefan Reinsch; Frank Schoeneich; Edmund A. M. Neugebauer; Ulf Elbelt (MDPI AG, 2024)
We examined the prevalence of obesity in two types of schools-a comprehensive school and a grammar school-in a rural German region of Brandenburg. Methods: In a cross-sectional study, BMI values were measured in 114 students in grades 5, 7, and 10. In addition to the demographic data, data on nutrition, physical activity, and mental well-being were collected using a questionnaire. Results: A total of 44% (11/25) of the comprehensive school students and 15% (13/89) of the high school students are overweight, and 24% (6/25) of the comprehensive school pupils and 6% (5/89) of the grammar school pupils (p = 0.009) are obese. In addition, 91% (10/11) of the students with obesity, 36% (4/11) of the students with pre-obesity, and 31% (26/84) of the normal-weight students (p = 0.001) are concerned about their weight. Among the children with obesity, 82% (9/11) are afraid of gaining weight. In addition, 6% (5/82) of the normal-weight students, 25% (3/12) of the students with pre-obesity, and 70% (7/10) of the students with obesity feel restricted by their weight when exercising. Conclusion: School attendance and parental socioeconomic status appear to correlate with students' weight statuses. There is a high level of suffering, and they feel uncomfortable with their bodies and worry about weight regulation.